Production and Characterization of Thermostable Amylases from Bacillus Circulans Isolated from a Local Hot Spring - Syed Aliee, Sharifah Srahrul Rabiah (1992)
Twos trains of amylolytic Bacillus were isolated from a hot spring in Negeri Sembilan and were identified as Bacillus circulans and designated as strains 8B-l and SB-21. The optimal temperature and pH for growth and enzyme production by boths trains were found to beat 55°C and pH 7.0, respectively. The enzyme was produced from the beginning of growth and reached maximum production at 72 hours. The production of amylase was partially induced and production occurred only in the presence of 1% starch.The presence of 20 mM maltose or malotriose enhanced enzyme production. The production was found to be repressed by 20 mM glucose. The crude enzyme preparation of 88-1 was purified through ion-exchange chromatography after 20-40% ammonium sulfate precipitation and ultrafiltration. A single activity peak and 31.6% yield was obtained with a 53.9 fold purification. Using SDS-PAGE the enzyme was shown to be homogenous and the molecular weight of the purified amylase was estimated to be about 60,000 dalton. The optimum temperature and pH for the activity of the purified amylase were shown to be 70°C and pH 5-9 respectively. The purified enzyme was less stable at higher temperature but 1mM CaCl2 stabilizes it significantly. The purified enzyme has higher affinity towards longer chain dextrins and more complex substrates such as starch . Thin-layer chromatography of enzymatic hydrolysis on various starches and dextrins indicated that the purified amylase behaves similar to that of a-amylase.